Exploration of an Efficient Electroporation System for Heterologous Gene Expression in the Genome of Methanotroph - Hu, Lizhen; Guo, Shuqi; Yan, Xin; Zhang, Tianqing; Xiang, Jing; Fei, Qiang (Frontiers in Microbiology, 2021)
One-carbon (C1) substrates such as methane or methanol have been considered as the next-generation carbon source in industrial biotechnology with the characteristics of low cost, availability, and bioconvertibility. Recently, methanotrophic bacteria naturally capable of converting C1 substrates have been drawn attractive attention for their promising applications in C1-based biomanufacturing for the production of chemicals or fuels. Although genetic tools have been explored for metabolically engineered methanotrophs construction, the efficient methods for heterologous gene expression in methanotrophs are still lacking. Here, a rapid and efficient electroporation method with a high transformation efficiency was developed for a robust methanotroph of Methylomicrobium buryatense 5GB1. Based on the homologous recombination and high transformation efficiency, gene deletion and heterologous gene expression can be simultaneously achieved by direct electroporation of PCR-generated linear DNA fragments. In this study, the influence of several key parameters (competent cell preparation, electroporation condition, recovery time, and antibiotics concentration) on transformation efficiency was investigated for optimum conditions. The maximum electroporation efficiency of 719 ± 22.5 cfu/µg DNA was reached, which presents a ten-fold improvement. By employing this method, an engineered M. buryatense 5GB1 was constructed to biosynthesize isobutyraldehyde by replacing an endogenous fadE gene in the genome with a heterologous kivd gene. This study provides a potential and efficient strategy and method to facilitate the cell factory construction of methanotrophs.